2009
DOI: 10.1097/ccm.0b013e3181b6ea1d
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle response to inflammation—Lessons for chronic obstructive pulmonary disease

Abstract: To describe how inflammation affects muscle adaptation and performance in people with chronic obstructive pulmonary disease. In chronic obstructive pulmonary disease, an increasingly sedentary lifestyle is a primary contributor to muscle dysfunction that results in a loss of mobility and independence and, ultimately, mortality. Given the systemic chronic inflammation and profound limb muscle atrophy in chronic obstructive pulmonary disease, it is tempting to speculate that the inflammatory process is deleterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 123 publications
(119 reference statements)
0
14
0
2
Order By: Relevance
“…ICU-acquired weakness is a common complication of critical illness with an incidence ranging from 25% to 58% depending on the patient population and diagnostic approach (30 -32). It is generally accepted that immobilization and inflammatory stimuli are important contributing factors to catabolism of muscle tissue (33) and ICU-acquired weakness (34). Despite the clinical significance of muscle atrophy for loss of function after discharge from intensive care (5), no preventive therapies have been identified as yet.…”
Section: Discussionmentioning
confidence: 99%
“…ICU-acquired weakness is a common complication of critical illness with an incidence ranging from 25% to 58% depending on the patient population and diagnostic approach (30 -32). It is generally accepted that immobilization and inflammatory stimuli are important contributing factors to catabolism of muscle tissue (33) and ICU-acquired weakness (34). Despite the clinical significance of muscle atrophy for loss of function after discharge from intensive care (5), no preventive therapies have been identified as yet.…”
Section: Discussionmentioning
confidence: 99%
“…Less clear is the ability of exercise training to improve systemic inflammation in COPD patients. We know that exercise can trigger an inflammatory response and oxidative stress in patients with COPD [49][50][51][52]. Noninjurious (moderate intensity and short duration) exercise increases the level of circulating inflammatory cells and cytokines, by stimulating interleukin (IL)-6, IL-10 and IL-1ra but inhibiting tumour necrosis factor (TNF)-a [53][54][55].…”
mentioning
confidence: 99%
“…The majority of the study participants were women, nonsmokers, non-drinkers, and relatively healthy, which lowers the external generalizability of the current results, especially to populations with lower physical function and more diseases. Considering previous studies that have reported associations between inflammation and decreased muscle strength among severely ill patients, such as those with sepsis or multiple organ failure [42, 43], possibility that phthalate exposure might lead to increased mortality due to weakened diaphragmatic muscle among individuals with lower physical function and more diseases [44] should be investigated in future studies. Second, although handgrip strength is a reliable indicator for whole-body muscle strength, direct measurement in the lower extremities would be more relevant to assess mobility and physical function in the elderly population [45].…”
Section: Discussionmentioning
confidence: 99%